Effect of alkali metal cations on dehydrogenative coupling of formate anions to oxalate - Tahara, Atsushi; Mori, Aska; Hayashi, Jun-ichiro; Kudo, Shinji (Frontiers in Chemistry, 2025)
IntroductionWith the growing global concern over CO2 emissions, reducing CO2 output has become an urgent requirement. The iron production industry is among those with the highest CO2 emissions, primarily due to the use of coke as a reductant and the use of a heat source at approximately 2,000°C. To address this issue, various alternative reductants, including CO, H2, and lignite, have been explored. Building on these efforts, we recently reported a novel ironmaking system using oxalic acid (HOOC–COOH) as the reductant. Formate salts, hydrogenated forms of CO2, are promising precursors for oxalate salts; however, their behavior during dimerization remains poorly understood. Herein, we investigate the influence of group 1 and 2 metal cations on the base-promoted dehydrogenative coupling of formate to form oxalate.MethodsFirst, dehydrogenative coupling of sodium formate was executed by using various types of groups 1 and 2 metal carbonates. Second, the base was replaced from metal carbonates to metal hydroxides to check the reactivity. Finally, a countercation of sodium formate was replaced to various types of groups 1 and 2 metals. To elucidate the reaction mechanism, DFT calculation was executed.Results and discussionTreatment of sodium formate with various bases (group 1 and 2 metal carbonates or hydroxides) revealed that group 1 metal hydroxides are more effective than metal carbonates for oxalate formation, with cesium hydroxide (CsOH) exhibiting high reactivity. Density functional theory (DFT) calculations suggest that this kinetic advantage arises not only from increased basicity but also from intermediate destabilization in the Na/Cs mixed-cation system. Additionally, both experimental and theoretical investigations reveal that oxalate yield is influenced by the thermodynamic stability of intermediates and products (oxalate salts), highlighting the crucial role of cations in the reaction.